2011
DOI: 10.1111/j.1601-0825.2010.01769.x
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β1 gene polymorphism in renal transplant patients with and without gingival overgrowth

Abstract: Oral Diseases (2011) 17, 414–419 Background:  The incidence of gingival overgrowth among renal transplant patients treated with cyclosporine A ranges from 13% to 84.6%, and the overgrowth is not only esthetic but also a medical problem. We studied the determination of association between TGF‐β1 (TGFB1) gene polymorphism and gingival overgrowth in kidney transplant patients medicated with cyclosporin A. Methods:  Eighty‐four kidney transplant patients with gingival overgrowth and 140 control transplant patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In addition to influential clinical factors, such as age, sex, the blood CsA concentration, the degree of renal injury, any drug combinations, and plaque-induced inflammation, studies have mainly focused on tissue fibrosis, oxidative stress, and the epithelial-tomesenchymal transition (EMT). 2,5,[10][11][12][13] The histopathological manifestations of drug-induced GO indicate that treatment with CsA thickens the gingival epithelium and increases the gingival fibroblasts in the lamina propria and collagen deposition. 14 It has been reported that CsA upregulates the expression of the fibrosis marker glutaminase 2 in gingival fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to influential clinical factors, such as age, sex, the blood CsA concentration, the degree of renal injury, any drug combinations, and plaque-induced inflammation, studies have mainly focused on tissue fibrosis, oxidative stress, and the epithelial-tomesenchymal transition (EMT). 2,5,[10][11][12][13] The histopathological manifestations of drug-induced GO indicate that treatment with CsA thickens the gingival epithelium and increases the gingival fibroblasts in the lamina propria and collagen deposition. 14 It has been reported that CsA upregulates the expression of the fibrosis marker glutaminase 2 in gingival fibroblasts.…”
Section: Introductionmentioning
confidence: 99%